KEBERADAAN TUHAN DALAM FILSAFAT NYĀYA DAN ARGUMEN KOSMOLOGI: Studi Komparasi Pandangan Ṛṣi Gautama dan Thomas Aquinas - Putu Dana Yasa (Pangkaja: Jurnal Agama Hindu, 2021)
The reality of God's existence is still a big question, especially for philosophers. Various attempts were made to acquire perfect knowledge of the existence of God. Various methods and arguments appear as a form of the activeness of the human mind in an effort to obtain the truth. One of the views that emerged and was considered logical was the view of i Gautama with the Nyaya philosophy which puts forward the logic and cosmological arguments of Thomas Aquinas' thought. These two views provide an understanding that God really exists and is the cause of everything that exists. These two views cannot be said to be perfect because they still raise questions about God as the ultimate reality that cannot be reached by human limitations. This paper tries to convey and elaborate the understanding of eastern and western philosophy about the existence of God by using the comparative method.